Method for improving production efficiency of all-titanium vanadium pellets
By mixing alkaline sintered return ore with vanadium-titanium magnetite and then performing steps such as drying, rolling, pelletizing, and roasting, the problems of compressive strength and ferrous oxide content in the traditional preparation of vanadium-titanium pellets have been solved, achieving efficient production and cost reduction.
Patent Information
- Application Number
- CN202411226776.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-01-10
AI Technical Summary
In the traditional vanadium-titanium pellet preparation process, the compressive strength of the finished pellets decreases, the ferrous oxide content increases, and there is a sugar core interlayer phenomenon, resulting in problems such as low production efficiency, high energy consumption, and high cost.
After mixing alkaline sintered return ore concentrate with vanadium-titanium magnetite, the mixture undergoes drying, rolling, pelletizing, and roasting to form vanadium-titanium pellets. Process parameters are optimized to improve the compressive strength and production efficiency of the pellets.
While ensuring the strength of the pellets is ≥2000N, it significantly improves production efficiency, reduces energy consumption and processing costs, and reduces the amount of recycled materials.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of metal smelting, and in particular relates to a method for improving the production efficiency of all-vanadium titanium pellets. Background Art
[0002] The main iron-containing mineral of vanadium-titanium magnetite in Panxi area is titanomagnetite, followed by granular ilmenite. Titanomagnetite is a complex composed of magnetite, ilmenite spar and magnesia-aluminum spinel. The ilmenite content in titanium concentrate is 92.12%, of which 99% of titanium exists in the form of ilmenite, and 96.01% of ilmenite exists as a monomer. At 400-500℃, the mineral components of vanadium-titanium magnetite begin to produce a series of solid-phase reactions: ilmenite and magnesia-aluminum spinel disappear, and the magnetite-ilmenite spar-magnesia-aluminum spinel solid solution separation structure gradually disappears, forming uniform titanium hematite and titanomagnetite, and the higher the temperature, the faster the formation speed.
[0003] The preparation of traditional vanadium-titanium pellets mostly adopts the process of mixing vanadium-titanium magnetite powder with a binder, and the mixture is balled and roasted to produce all-vanadium-titanium pellets. When the production line efficiency is improved, the compressive strength of the finished pellets will drop significantly (reduced by 200-300N), and the ferrous oxide content of the finished pellets will increase by about 1.0%-2.0%. There is a shiny "sugar core interlayer" phenomenon in the middle of the finished pellets, which makes it difficult to achieve vanadium-titanium magnetite enhanced roasting pellets, restricting the performance of the pellet production line capacity, resulting in high processing energy consumption and processing costs of all-vanadium-titanium pellets. Summary of the invention
[0004] The purpose of the present invention is to provide a method for improving the production efficiency of all-vanadium-titanium pellets. The method of the present invention can significantly improve the production efficiency of the pellet production line under the premise of ensuring that the strength of the vanadium-titanium pellets is ≥2000N.
[0005] The present invention provides a method for improving the production efficiency of all-vanadium titanium pellets, comprising the following steps:
[0006] A) grinding the alkaline sintered return ore to obtain alkaline sintered return ore concentrate;
[0007] B) mixing the alkaline sintered return ore concentrate with vanadium-titanium magnetite to obtain mixed iron ore powder;
[0008] C) drying and rolling the mixed iron ore powder to obtain treated mixed iron ore powder;
[0009] D) mixing the treated mixed iron ore powder, binder and pelletizing area dust, and pelletizing the mixture to obtain green pellets;
[0010] E) drying, preheating, roasting, soaking and cooling the green pellets to obtain all-vanadium titanium pellets.
[0011] Preferably, the particle size of the alkaline sintered return ore is 0-5 mm; and in the alkaline sintered return ore concentrate, particles with a particle size of less than 200 mesh account for 75-85%.
[0012] Preferably, in the mixed iron ore powder, the mass fraction of the alkaline sintered return ore concentrate is 2-5%, and the mass fraction of the vanadium-titanium magnetite is 95-98%.
[0013] Preferably, the moisture content of the mixed iron ore powder after treatment in step C) is ≤8.5%.
[0014] Preferably, in the mixed material in step D), the mass fraction of the treated mixed iron ore powder is 95-99%, the mass fraction of the binder is 0.5-3%, and the mass fraction of the pelletizing area dust is 0.5-2%.
[0015] Preferably, in step D), the mixing time is 40 to 180 seconds.
[0016] Preferably, the drying temperature in step E) is 280-400°C; the drying time in step E) is 3-4 minutes.
[0017] Preferably, the preheating temperature is 600-1000° C., and the preheating time is 10-20 min.
[0018] Preferably, the calcination temperature in step E) is 1220-1260° C., and the calcination time in step E) is 8-12 minutes.
[0019] Preferably, the temperature of the soaking in step E) is 1000-1150° C., and the time of the soaking in step E) is 3-6 minutes.
[0020] The present invention provides a method for improving the production efficiency of all-vanadium titanium pellets, comprising the following steps: A) grinding alkaline sintering return ore to obtain alkaline sintering return ore concentrate; B) mixing the alkaline sintering return ore concentrate with vanadium titanium magnetite to obtain mixed iron ore powder; C) drying and rolling the mixed iron ore powder to obtain treated mixed iron ore powder; D) mixing the treated mixed iron ore powder, a binder and dust removal ash from the pelletizing area, and pelletizing the mixture to obtain green pellets; E) drying, preheating, roasting, homogenizing and cooling the green pellets to obtain all-vanadium titanium pellets. The method of the present invention can greatly improve the production efficiency of vanadium titanium magnetite pellets, and can realize vanadium titanium magnetite enhanced roasting pellets on the premise of ensuring that the strength of vanadium titanium pellets is ≥2000N, significantly improve the production efficiency of the pellet production line, reduce the energy consumption and processing cost of the vanadium titanium pellet production process, and at the same time, reduce the amount of circulating materials in the sintering production process and reduce the processing cost of the sintering process. DETAILED DESCRIPTION
[0021] The present invention provides a method for improving the production efficiency of all-vanadium-titanium pellets, comprising the following steps:
[0022] A) grinding the alkaline sintered return ore to obtain alkaline sintered return ore concentrate;
[0023] B) mixing the alkaline sintered return ore concentrate with vanadium-titanium magnetite to obtain mixed iron ore powder;
[0024] C) drying and rolling the mixed iron ore powder to obtain treated mixed iron ore powder;
[0025] D) mixing the treated mixed iron ore powder, binder and pelletizing area dust, and pelletizing the mixture to obtain green pellets;
[0026] E) drying, preheating, roasting, soaking and cooling the green pellets to obtain all-vanadium titanium pellets.
[0027] In the present invention, the particle size of the alkaline sintered return ore is preferably 0-5 mm, and the powder with a particle size of less than 200 mesh in the alkaline sintered return ore concentrate after grinding preferably accounts for 75-85%, more preferably 80%. The present invention has no special restrictions on the grinding method, and the ore grinding method commonly used in the art can be used.
[0028] After obtaining the alkaline sintering return ore concentrate, the present invention mixes the alkaline sintering return ore concentrate with vanadium-titanium magnetite to obtain mixed iron ore powder.
[0029] In the present invention, in the mixed iron ore powder, the mass fraction of the alkaline sintered return ore concentrate is preferably 2-5%, more preferably 3-4%, such as 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, preferably a range value with any of the above values as the upper or lower limit; the mass fraction of the vanadium-titanium magnetite is preferably 95-98%, more preferably 96-97%, such as 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, preferably a range value with any of the above values as the upper or lower limit.
[0030] In the present invention, the mixing time of the alkaline sintered return ore concentrate and the vanadium-titanium magnetite is preferably 40 to 70 seconds, more preferably 50 to 60 seconds.
[0031] After obtaining the mixed iron ore powder, the present invention dries and rolls the mixed iron ore powder to obtain the treated mixed iron ore powder.
[0032] In the present invention, the drying temperature is preferably 280-400°C, more preferably 300-350°C, such as 280°C, 300°C, 320°C, 350°C, 380°C, 400°C, preferably a range value with any of the above values as the upper or lower limit; the drying time is preferably 3-4 min.
[0033] In the present invention, the roller pressing can increase the specific surface area and surface activation energy of the material, and improve the material ball-forming performance index.
[0034] In the present invention, the moisture content of the treated mixed iron ore powder is preferably ≤8.5%.
[0035] After obtaining the mixed iron ore powder, the present invention mixes the treated mixed iron ore powder, a binder and dust removal ash from the pelletizing area, and pelletizes the mixture to obtain green pellets.
[0036] In the present invention, the mixing time is preferably 40 to 180 s, more preferably 50 to 150 s, such as 40 s, 50 s, 60 s, 70 s, 80 s, 90 s, 100 s, 110 s, 120 s, 130 s, 140 s, 150 s, 160 s, 170 s, 180 s, preferably a range value with any of the above values as the upper or lower limit.
[0037] In the present invention, in the mixture, the mass fraction of the treated mixed iron ore powder is preferably 95-99%, more preferably 96-98%, such as 95%, 95.5%, 96%, 96.5%, 97%, 97.5%, 98%, 98.5%, 99%, preferably a range value with any of the above values as the upper or lower limit; the binder is preferably bentonite; the mass fraction of the binder is preferably 0.5-3%, more preferably 1-2.5%, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, preferably a range value with any of the above values as the upper or lower limit; the mass fraction of the dust removal ash in the pelletizing area is preferably 0.5-2%, more preferably 1-1.5%, such as 0.5%, 1%, 1.5%, 2%, preferably a range value with any of the above values as the upper or lower limit.
[0038] In the present invention, the pelletizing is preferably carried out using a disc pelletizing machine, the feeding capacity of a φ6m pelletizing disc is ≥60t / h, the feeding capacity of a φ7.5m pelletizing disc is ≥90t / h, the number of times the raw pellets fall is 5 to 7 times, and the proportion of 9 to 14mm particle size in the raw pellets is ≥80%.
[0039] After obtaining the green pellets, the present invention preferably uses a belt roaster to sequentially dry, preheat, roast, soak and cool the green pellets to obtain all-vanadium titanium pellets.
[0040] In the present invention, the drying temperature is preferably 280-400°C, more preferably 300-350°C, such as 280°C, 300°C, 320°C, 350°C, 380°C, 400°C, preferably a range value with any of the above values as the upper or lower limit; the drying time is preferably 3-4 minutes.
[0041] In the present invention, the preheating temperature is preferably 600-1000°C, more preferably 700-900°C, such as 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C, preferably a range value with any of the above values as the upper or lower limit; the preheating time is preferably 10-20 min, more preferably 12-18 min.
[0042] In the present invention, the calcination temperature is preferably 1220-1260°C, more preferably 1240-1250°C, such as 1220°C, 1230°C, 1240°C, 1250°C, 1260°C, preferably a range value with any of the above values as the upper or lower limit; the calcination time is preferably 8-12 min, more preferably 10-11 min.
[0043] In the present invention, the soaking temperature is preferably 1000-1150° C., more preferably 1050-1100° C.; the soaking time is preferably 3-6 min, more preferably 4-5 min.
[0044] After the equalization is completed, the present invention preferably uses natural air to cool the pellets to ≤120°C.
[0045] The present invention provides a method for improving the production efficiency of all-vanadium titanium pellets, comprising the following steps: A) grinding alkaline sintering return ore to obtain alkaline sintering return ore concentrate; B) mixing the alkaline sintering return ore concentrate with vanadium titanium magnetite to obtain mixed iron ore powder; C) drying and rolling the mixed iron ore powder to obtain treated mixed iron ore powder; D) mixing the treated mixed iron ore powder, a binder and dust removal ash from the pelletizing area, and pelletizing the mixture to obtain green pellets; E) drying, preheating, roasting, soaking and cooling the green pellets to obtain all-vanadium titanium pellets. The method of the present invention can greatly improve the oxidation rate of vanadium titanium magnetite pellets, shorten the oxidation preheating time, and realize the vanadium titanium magnetite strengthened roasting pellets on the premise of ensuring that the strength of the vanadium titanium pellets is ≥2000N, significantly improve the production efficiency of the pellet production line, reduce the energy consumption and processing cost of the vanadium titanium pellet production process, and at the same time, reduce the amount of circulating materials in the sintering production process and reduce the processing cost of the sintering process.
[0046] In order to further illustrate the present invention, a method for improving the production efficiency of all-vanadium titanium pellets provided by the present invention is described in detail below in conjunction with examples, but it should not be understood as limiting the scope of protection of the present invention.
[0047] Example 1
[0048] The alkaline sintered return ore with a particle size of 0-5mm is finely ground into fine powder with a particle size of <200 mesh accounting for about 80% through dry grinding process;
[0049] In the pre-batch process, the alkaline sintering return ore concentrate powder and vanadium-titanium magnetite are mixed together to form mixed iron powder, and the batching structure is: vanadium-titanium magnetite 97% + alkaline sintering return ore concentrate powder 3%;
[0050] The mixed iron ore powder is dried at 800°C for 6 minutes and roller pressed to control the moisture content of the mixed iron ore powder to be less than 8.5% after drying;
[0051] According to the ingredients structure of "mixed iron ore powder 97.5% + binder 1.5% + pellet area dust removal 1%", mix in a powerful mixer for about 60s;
[0052] The mixture is pelletized using a disc pelletizer, using a single disc of φ7.5m, with a feed rate of 100±20t / h, and the number of falling times of the prepared green pellets is 6±1 times, and the proportion of 9-14mm particle size in the green pellets is ≥80%;
[0053] The raw pellets are fed into a belt roaster and dried, preheated, roasted and evenly heated according to the temperature control requirements of each process section. The drying temperature is 290±30℃, the drying time is 3±1min, the preheating temperature is 700±250℃, the preheating time is 16±1min, the roasting temperature is 1240±20℃, the roasting time is 9±1min, the evenly heated temperature is 1100±100℃, the evenly heated time is 3±1min, and all-vanadium titanium pellets are obtained after cooling.
[0054] Example 2
[0055] The alkaline sintered return ore with a particle size of 0-5mm is finely ground into fine powder with a particle size of <200 mesh accounting for about 80% through dry grinding process;
[0056] In the pre-batch process, the alkaline sintering return ore concentrate powder and vanadium-titanium magnetite are mixed together to form mixed iron powder, and the batching structure is: vanadium-titanium magnetite 95% + alkaline sintering return ore concentrate powder 5%;
[0057] The mixed iron ore powder is dried at 800°C for 6 minutes and roller pressed to control the moisture content of the mixed iron ore powder to be less than 8.5% after drying;
[0058] According to the ingredients structure of "mixed iron ore powder 97.5% + binder 1.5% + pellet area dust removal 1%", mix in a powerful mixer for about 60s;
[0059] The mixture is pelletized using a disc pelletizer, using a single disc of φ7.5m, with a feed rate of 100±20t / h, and the number of falling times of the prepared green pellets is 6±1 times, and the proportion of 9-14mm particle size in the green pellets is ≥80%;
[0060] The raw pellets are fed into a belt roaster and dried, preheated, roasted and evenly heated according to the temperature control requirements of each process section. The drying temperature is 290±30℃, the drying time is 3±1min, the preheating temperature is 700±250℃, the preheating time is 16±1min, the roasting temperature is 1240±20℃, the roasting time is 9±1min, the evenly heated temperature is 1100±100℃, the evenly heated time is 3±1min, and all-vanadium titanium pellets are obtained after cooling.
[0061] Comparative Example 1
[0062] All-vanadium-titanium pellets were prepared according to the steps in Example 1, except that no alkaline sintering return ore was added in Comparative Example 1, and an equal amount of vanadium-titanium magnetite was directly used instead of the mixed iron ore powder.
[0063] The performance of the all-vanadium titanium pellets obtained in the examples and comparative examples was tested, and the results are shown in Table 1:
[0064] Table 1 Performance data of all-vanadium titanium pellets in embodiments and comparative examples
[0065] Comparative Example 1 Example 1 Example 2 Compressive strength(N) 1700 2082 2013 <![CDATA[Utilization factor (t / m 2 ·h)]]> 0.82 0.933 0.931
[0066] In Table 1, utilization coefficient = output ÷ operation time ÷ total area of belt roasting machine exhaust bellows) According to the data in Table 1, it can be seen that the method in the present invention can greatly improve the compressive strength index of the finished pellets while ensuring a certain output of the pellets; and can greatly improve the output index of the finished pellets while ensuring a certain strength index (compressive strength) of the pellets.
[0067] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for improving the production efficiency of all-vanadium titanium pellets, comprising the following steps: A) grinding the alkaline sintered return ore to obtain alkaline sintered return ore concentrate; B) mixing the alkaline sintered return ore concentrate with vanadium-titanium magnetite to obtain mixed iron ore powder; C) drying and rolling the mixed iron ore powder to obtain treated mixed iron ore powder; D) mixing the treated mixed iron ore powder, binder and pelletizing area dust, and pelletizing the mixture to obtain green pellets; E) drying, preheating, roasting, soaking and cooling the green pellets to obtain all-vanadium titanium pellets.
2. The method according to claim 1, characterized in that The particle size of the alkaline sintered return ore is 0-5 mm; in the alkaline sintered return ore concentrate, particles with a particle size of less than 200 mesh account for 75-85%.
3. The method according to claim 1, characterized in that In the mixed iron ore powder, the mass fraction of the alkaline sintered return ore concentrate is 2-5%, and the mass fraction of the vanadium-titanium magnetite is 95-98%.
4. The method according to claim 1, characterized in that: The moisture content of the mixed iron ore powder after being treated in step C) is ≤8.5%.
5. The method according to claim 1, characterized in that In the mixed material in step D), the mass fraction of the treated mixed iron ore powder is 95-99%, the mass fraction of the binder is 0.5-3%, and the mass fraction of the pelletizing area dust is 0.5-2%.
6. The method according to claim 1, characterized in that In the step D), the mixing time is 40 to 180 seconds.
7. The method according to claim 1, characterized in that The drying temperature in the step E) is 280-400° C.; the drying time in the step E) is 3-4 minutes.
8. The method according to claim 1, characterized in that The preheating temperature is 600-1000° C., and the preheating time is 10-20 minutes.
9. The method according to claim 1, characterized in that: The calcination temperature in the step E) is 1220-1260° C., and the calcination time in the step E) is 8-12 minutes.
10. The method according to claim 1, characterized in that The temperature of the soaking in the step E) is 1000-1150° C., and the time of the soaking in the step E) is 3-6 minutes.